2017
DOI: 10.1002/jtr.2117
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effects of tourist policy adjustments on the development of tourism in Taiwan: Consideration of time trends and Fourier component test results

Abstract: Previous studies have argued that tourism policy has a long‐term positive relationship with tourism development. This study explored temporal trends in and seasonal effects of the number of tourists traveling to Taiwan between 2001 and 2016, and compared the effects of adjustments in tourism policy on tourism development to determine whether Taiwan's international tourism policies have had long‐term effects on tourism development. Temporal trends and seasonal factors were not significantly related to adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Our results also reveal that the distance between Taiwan and the country of origin ( DT t ) has a significantly negative impact on both non-Chinese and Chinese tourists, which is in line with the findings of the prior studies; that is, the shorter the distance between Taiwan and the country of origin—which obviously implies lower transportation costs and traveling time—the greater the number of inbound tourists traveling to Taiwan from that country. Finally, we show that under all of our econometric methods, the outbreak of the SARS epidemic in 2003 (as measured by D _2003) had a strictly significant negative effect, a finding that is in line with the results reported by Tseng and Huang (2017).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Our results also reveal that the distance between Taiwan and the country of origin ( DT t ) has a significantly negative impact on both non-Chinese and Chinese tourists, which is in line with the findings of the prior studies; that is, the shorter the distance between Taiwan and the country of origin—which obviously implies lower transportation costs and traveling time—the greater the number of inbound tourists traveling to Taiwan from that country. Finally, we show that under all of our econometric methods, the outbreak of the SARS epidemic in 2003 (as measured by D _2003) had a strictly significant negative effect, a finding that is in line with the results reported by Tseng and Huang (2017).…”
Section: Resultssupporting
confidence: 89%
“…On the one hand, such a policy might well boost the construction of tourism infrastructure and facilities in Taiwan, potentially improving the capacity and quality of Taiwan tourism services and eventually attracting more international arrivals to Taiwan. For example, using inbound tourism data on Taiwan over the 2001–2016 period, Tseng and Huang (2017) demonstrated that the opening policy increased the numbers of tourists from Hong Kong and Macau, with no crowding-out effect being discernible on Japanese tourists traveling to Taiwan. On the other hand, however, the capacity or quality of tourism services could decline if the increase in tourism infrastructure and facilities in Taiwan was unable to keep up with the growth in Chinese tourist numbers; this could result in lowering the attractiveness of Taiwan to international inbound tourists and a resultant decline in international tourism numbers.…”
Section: Factors Affecting Tourism In Taiwanmentioning
confidence: 99%
See 2 more Smart Citations
“…This exploration goes beyond consumer behavior to examine how economic indicators also predict rates of tourism development itself [24], an extension of the long tradition of research into the determinants of tourism flows. There is a growing body of research that explores how macroeconomic conditions influence tourist behavior and tourism development.…”
Section: Determinants Of Tourism Demandmentioning
confidence: 99%